2012
DOI: 10.1177/0273475312457781
|View full text |Cite
|
Sign up to set email alerts
|

A Tutorial Guide About How to Manage a Client-Financed Project

Abstract: Client-based/sponsored projects are one of the best ways to provide students with a valuable learning experience (Bove & Davies, 2009; Parsons & Lepkowska-White, 2009). Experiential learning is "learning by experience." As Evans and Lang (2006) suggested, experiential learning is an action strategy where the student is directly in touch with real things and people or is involved in activities that simulate real activities or people. Students will come into contact with exactly what they are learning. A client-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Moore (2010) suggested that the transformative effects of experiential learning require it be “structured effectively and processed rigorously” (p. 11). Numerous scholars have proposed processes and guidance for constructing and managing CBPs (Bove & Davis, 2009; Clark, King, & Jurn, 2012; de los Santos & Jensen, 1985; Lopez & Lee, 2005; Muir, 1996; Strauss, 2011; West, 2011). These approaches generally align to the traditional view of project management as groups of sequential processes: (1) project initiation, (2) project planning, (3) project execution, (4) project monitoring and control, and (5) project closure (Project Management Institute, 2008).…”
Section: Cbp Processes and Task Structurementioning
confidence: 99%
See 2 more Smart Citations
“…Moore (2010) suggested that the transformative effects of experiential learning require it be “structured effectively and processed rigorously” (p. 11). Numerous scholars have proposed processes and guidance for constructing and managing CBPs (Bove & Davis, 2009; Clark, King, & Jurn, 2012; de los Santos & Jensen, 1985; Lopez & Lee, 2005; Muir, 1996; Strauss, 2011; West, 2011). These approaches generally align to the traditional view of project management as groups of sequential processes: (1) project initiation, (2) project planning, (3) project execution, (4) project monitoring and control, and (5) project closure (Project Management Institute, 2008).…”
Section: Cbp Processes and Task Structurementioning
confidence: 99%
“…Relative to timing, the application of studied theory in a CBP can occur either concurrent with the studied theory (Clark et al, 2012; West, 2011) or succedent, applying previously studied theory such as a capstone model (Gorman, 2011; Strauss, 2011). As the principal course we identified for consistent use of CBPs was the core MBA Marketing Management course, concurrent timing was deemed most appropriate.…”
Section: Creating a Cbp Suprastructurementioning
confidence: 99%
See 1 more Smart Citation
“…For example, experiential learning activities such as “live” or “real-world” cases, exercises, or projects offer a promising variation to the traditional case method (Corrigan & Cracium, 2012). These activities foster perceptions of critical thinking skills by situating students’ problem solving in a real business environment (Clark, King, & Jurn, 2012), thereby increasing students’ motivation for learning (Lopez & Gravois, 2005). Similarly, service learning projects help engage students in reflection, critical thinking, knowledge application, and practical lessons in civic responsibility (Geringer, Stratemeyer, Canton, & Rice, 2009).…”
Section: Integrative Framework For Investigating Critical Thinking Skmentioning
confidence: 99%
“…There are similar field-based courses in related fields such as marketing (see Clark et al 2012) and Engineering (Mosher 2014).…”
Section: Introductionmentioning
confidence: 99%